An Analysis of Listening Skill Difficulties Faced by Children of Indonesian Migrant Workers in Malaysia - Nur Ain Nun; Diah Safithri Armin (Institut Agama Islam Negeri Palopo, 2025)
This study explores the difficulties in English language comprehension faced by children of Indonesian migrant workers in Malaysia. Using a descriptive qualitative approach, data were collected through questionnaires and interviews with sixth-grade students in a non-formal education center. The findings reveal five major challenges: (1) multilingual environment, which hinders English language comprehension due to the influence of other languages; (2) limited access to education, resulting in difficulties in English language comprehension due to inadequate facilities and resources; (3) social and economic factors, which impede English language comprehension due to limited access to technology and internet; (4) lack of authentic English exposure, leading to difficulties in English language comprehension due to insufficient exposure to authentic English language; and (5) psychological factors, including motivation and self-confidence, which affect English language comprehension due to anxiety and low self-esteem. These factors are interrelated and rooted in the students’ linguistic environment, educational infrastructure, and socio-emotional context. The study underscores the need for inclusive, context-responsive instructional strategies and improved educational support systems to enhance the English listening skills of marginalized learners.